Immigrant welfare receipt across Europe - Alan Barrett; Bertrand Maître (Institute for the Study of Labor (IZA), 2011)
The issue of welfare receipt by immigrants is highly controversial across Europe. In this paper, we assess whether immigrants are more likely to receive welfare payments relative to natives across a range of European countries. Using the European Union Survey on Income and Living Conditions for 2007, we find very little evidence that immigrants are indeed more likely to receive such payments when all payments are considered together. This is true whether we use raw data or regression analysis in which we control for relevant characteristics. We do find evidence of higher rates of poverty among immigrants. When combined with the results on welfare receipt, this raises a question over the effectiveness of welfare systems in protecting immigrants from poverty across Europe.
urn:nbn:de:101:1-201104113889
Keywords: I38; J61; 330; welfare; immigrants; Europe; Migranten; Sozialhilfeempfänger; Armut; Sozialpolitik; EU-Staaten